Differentiated English Learning Material for Elementary School Students - Ariani, Pande Made Mela; Mahayanti, Ni Wayan Surya; Budiarta, Luh Gd Rahayu (STKIP AGAMA HINDU SINGARAJA, 2024)
This study aimed at developing additional materials for digital English textbooks that are differentiated according to the Merdeka curriculum for fifth-grade students in Denpasar schools. By following the D&D method which uses the ADDE (analysis, Design, Development and Evaluation) model from Richey Klein (2014), the data in this study were analyzed using a mixed method, namely quantitative and qualitative analysis. This study explains the defiance presented in the manual so that additional materials are developed based on student needs. The research process begins with analyzing the textbook then compiling a blueprint that will be used in designing additional materials then developing the materials through the Canva application and evaluating those provided by experts and teachers related to additional digital materials. The results show that the material is very effective and suitable for use in fifth-grade elementary schools because the material is in accordance with the students' learning styles. This study was conducted to provide information to educators, researchers in developing differentiated materials according to the Emancipated curriculum and the needs desired by students in the learning process in the classroom through digital media.